Sosialisasi dan Pelatihan Herbisida Alami Berbasis Bahan Lokal bagi Masyarakat Desa Peron untuk Pengendalian Gulma pada Sistem Agroforestry - Haris, Amnan; Trida Ridho, Fariz; Amelia, Rizki Nor; Rahayu, Ayu; Ismiyati, Titik; Alma’ruf, Fattah; Naufal, Muhammad Agnaf; Pradama, Daffa Evan; Revalina, Aurelia Dias Nanda; Najwa, Rizqa (Universitas Negeri Semarang, 2025)
Abstract Peron Village located on the western slopes of Mount Ungaran at an altitude of 700 meters above sea level, is in the upstream area of the Bodri Watershed, a priority watershed. Despite implementing an agroforestry system that combines forestry and agricultural crops, local farmers still rely heavily on synthetic herbicides containing glyphosate for weed control. This dependence poses serious risks to water quality, aquatic ecosystems, and the health of communities that rely on spring water. This community service program aims to improve ecological literacy and practical skills in making environmentally friendly herbicides using local ingredients such as coarse salt, vinegar, and sulfur. The activity was held at the Peron Village Hall with 25 participants representing the hamlets. The program included socialization of the concept of agroforestry, the theory of natural herbicides, and the practice of making organic herbicides using 1 liter of clean water, 500 g of coarse salt, 0.75 ounces of sulfur, and 100 ml of vinegar. The results showed that participants successfully produced an effective natural herbicide that controlled weeds within two days, albeit slower than synthetic herbicides, without damaging soil structure or polluting water sources. This success opens up opportunities for further development by utilizing agroforestry waste such as coffee husks as active ingredients, supporting the zero-waste concept and increasing the economic value of local commodities. This program aligns with the Sustainable Development Goals and can be replicated in other agroforestry areas in Indonesia.